Chambers & Partners global : the world's leading lawyers - Chambers & Partners (London : Chambers & Partners Publishing, 1999)
The Chambers Global Guide ranks the top lawyers and law firms in over 190 countries across the world. The rankings are based on the in-depth research of dedicated and experienced team of researchers.
Subtitle varies.
From <2013> issued in 2 volumes.
Includes indexes
oif 24/10/2019
Ref.
Keywords: Law firms---Directories.; Lawyers---Directories.; Corporate lawyers---Directories.; Corporation law; Commercial law; International law